Teacher interaction enhances engagement and motivation in game-centered basketball learning - Hidayah, Taufiq; Akhiruyanto, Andry; Yudhistira, Dewangga; Virama, La Ode Adhi (Jurnal Cakrawala Pendidikan, 2025)
Teacher interaction is critical for improving student engagement and motivation in Game-Centered Approach (GCA)-based basketball learning.  The purpose of this study was to examine how teacher interaction affects student engagement and motivation within this pedagogical framework.  This study utilized a quasi-experimental design with junior high school students as participants.  The experimental group received improved teacher interaction strategies, such as providing feedback, asking reflective questions, and fostering discussions, whereas the control group used conventional learning methods. Data were collected using pre-and post-test questionnaires, classroom observations, and structured interviews.  The results revealed a significant increase in student engagement and motivation in the experimental group compared to the control group (p = 0.000).  Statistical analysis utilizing paired t-tests and independent t-tests confirmed that teacher interaction in GCA-based basketball learning improved students' learning outcomes.  This study underlines the relevance of teachers as facilitators for improving student participation and motivation.